Emotional- and cognitive-like responses induced by social defeat stress in male mice are modulated by the BNST, amygdala, and hippocampus - da Costa, Vinícius Fresca; Ramírez, Johana Caterin Caipa; Ramírez, Stephany Viatela; Avalo-Zuluaga, Julian Humberto; Baptista-de-Souza, Daniela; Canto-de-Souza, Lucas; Planeta, Cleopatra S.; Rodríguez, Javier Leonardo Rico; Nunes-de-Souza, Ricardo Luiz (Frontiers in Integrative Neuroscience, 2023)
Introduction Chronic exposure to social defeat stress (SDS) has been used to investigate the neurobiology of depressive- and anxiety-like responses and mnemonic processes. We hypothesized that these affective, emotional, and cognitive consequences induced by SDS are regulated via glutamatergic neurons located in the bed nucleus of the stria terminalis (BNST), amygdaloid complex, and hippocampus in mice. Methods Here, we investigated the influence of chronic SDS on (i) the avoidance behavior assessed in the social interaction test, (ii) the anxiety-like behavior (e.g., elevated plus-maze, and open field tests) (iii) depressive-like behaviors (e.g., coat state, sucrose splash, nesting building, and novel object exploration tests), (iv) the short-term memory (object recognition test), (v) ΔFosB, CaMKII as well as ΔFosB + CaMKII labeling in neurons located in the BNST, amygdaloid complex, dorsal (dHPC) and the ventral (vHPC) hippocampus. Results The main results showed that the exposure of mice to SDS (a) increased defensive and anxiety-like behaviors and led to memory impairment without eliciting clear depressive-like or anhedonic effects; (b) increased ΔFosB + CaMKII labeling in BNST and amygdala, suggesting that both areas are strongly involved in the modulation of this type of stress; and produced opposite effects on neuronal activation in the vHPC and dHPC, i.e., increasing and decreasing, respectively, ΔFosB labeling. The effects of SDS on the hippocampus suggest that the vHPC is likely related to the increase of defensive- and anxiety-related behaviors, whereas the dHPC seems to modulate the memory impairment. Discussion Present findings add to a growing body of evidence indicating the involvement of glutamatergic neurotransmission in the circuits that modulate emotional and cognitive consequences induced by social defeat stress.